Teachers training in design digital-based authentic assessments to support differentiated learning in transformative school - Euis Nursaadah; Aceng Ruyani; Bhakti Karyadi; Elsi Adelia Fitri (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
Training digital-based authentic assessments is essential due to decontextualization challenges and technological advancements in learning assessment. Transformative schools require teachers to design innovative assessments supporting differentiated learning in the independent curriculum implementation, yet many face difficulties in creating assessments aligned with new learning paradigms. This study implemented the ICARE framework (Introduction, Connection, Application, Reflection, and Extend) to enhance teachers' competencies in designing digital-based authentic assessments at SMPN 02 Tebat Karai and SMPN 02 Kepahiang. Thirty teachers from various subjects with 1-20+ years of teaching experience participated in this professional development program. Data were collected through Socrative application reflection and semi-structured interviews, analyzed descriptively across three experience groups. Results showed that most teachers successfully implemented the independent curriculum and demonstrated proficiency in diagnostic, formative, and summative assessments. Observation and project assessments were most widely used during learning processes. Teachers exhibited competence with digital tools including Google Forms, Quizizz, and Socrative. Assessment preferences varied across experience groups, with performance and portfolio assessments predominating. The ICARE framework effectively developed teachers' competencies in designing digital-based authentic assessments aligned with learning objectives and differentiated learning principles. This study contributes practical frameworks for teacher professional development in authentic assessment within Indonesian transformative school contexts, providing evidence-based guidelines for enhancing assessment literacy. Future research should investigate long-term impacts on student learning outcomes and explore scalability across diverse educational settings.